Phosphorus and naphthalene acetic acid increased the seed yield by regulating carbon and nitrogen assimilation of flax - Xie, Yaping; Duan, Huirong; Wang, Limin; Zhang, Jianping; Dong, Kongjun; Wang, Xingrong; Zhang, Yanjun; Zhou, Yangchen; Li, Wenjuan; Qi, Yanni; Zhao, Wei; Dang, Zhao; et al. (Frontiers in Plant Science, 2023)
To evaluate the impact of phosphorus (P) combined with exogenous NAA on flax yield, enhance flax P utilization efficiency and productivity, minimize resource inputs and mitigate negative environmental and human effects. Therefore, it is crucial to comprehend the physiological and biochemical responses of flax to P and naphthylacetic acid (NAA) in order to guide future agronomic management strategies for increasing seed yield. A randomized complete block design trial was conducted under semi-arid conditions in Northwest China, using a factorial split-plot to investigate the effects of three P (0, 67.5, and 135.0 kg P2O5 ha–1) and three exogenous spray NAA levels (0, 20, and 40 mg NAA L–1) on sucrose phosphate synthase (SPS) and diphosphoribulose carboxylase (Rubisco) activities as well as nitrogen (N) and P accumulation and translocation in flax. Results indicated that the SPS and Rubisco activities, N and P accumulation at flowering and maturity along with assimilation and translocation post-flowering, fruiting branches per plant, tillers per plant, capsules per plant, and seed yield were 95, 105, 14, 27, 55, 15, 13, 110, 103, 82, 16, 61, 8, and 13% greater in the P treatments compared to those in the zero P treatment, respectively. Moreover, those characteristics were observed to be greater with exogenous spray NAA treatments compared to that no spray NAA treatment. Additionally, the maximum SPS and Rubisco activities, N and P accumulation, assimilation post-flowering and translocation, capsules per plant, and seed yield were achieved with the application of 67.5 kg P2O5 ha–1 with 20 mg NAA L–1. Therefore, these findings demonstrate that the appropriate combination of P fertilizer and spray NAA is an effective agronomic management strategy for regulating carbon and nitrogen assimilation by maintaining photosynthetic efficiency in plants to increase flax productivity.